Eficiência do uso do fósforo pela melancia (cv. ‘Magnum’) sob adubações fosfatadas em fundação e fertirrigação - Alves Júnior, Antônio Roberto (Universidade Federal Rural do Semi-Árido, 2017)
Watermelon has a major social and economic importance for the state of Rio Grande do Norte, Brazil, especially the agricultural region of Assú-Mossoró, generating revenues, jobs and playing an important role to keep farmers in the field. However, local farmers do not have the information about necessary nutrient dosage to achieve maximum watermelon yield, mainly regarding to the new hybrids introduced in the area. This way, the majority of producers end up applying high fertilizer doses, higher than the necessary for maximum yield, increasing production costs and harm to the environment, which may turn this in an unsustainable practice. In this context, this study aimed to evaluate the efficiency of phosphorus in watermelon cultivated under different doses in foundation and fertigation. For this purpose, watermelon cultivar ‘Magnum’ was planted in Upanema-RN, during the period from September to December, in 2013. Experimental design of randomized blocks, factorial scheme (4x2) + 1, with four replications, composed respectively of four phosphorus doses (76, 168, 275, and 397 kg/ha of P2O5), two application forms [foundation, and foundation + fertigation], and one additional treatment with no phosphorus. The fertilization in foundation with the dose of 76 kg/ha presented the highest values for physiologic efficiency and P use efficiency. However, for agronomic efficiency and apparent recovery efficiency there was no significant difference between forms of application, only for dosage. The dosage which showed most increment in efficiencies was 76 kg/ha of P2O5, but maximum yield was obtained with an estimated dose of 290 kg/ha.
Monografia
Keywords: Citrullus lanatus; Eficiência; Fósforo; Citrullus lanatus; Efficiency; Phosphorus; CIENCIAS AGRARIAS::AGRONOMIA